Psychosocial factors, but not professional practice skills, linked to self‐perceived effectiveness of telepractice in school‐based speech and language therapists during COVID‐19 pandemic - Lam, Joseph Hin Yan; Chiu, Ming Ming; Lee, Stephen Man Kit; Tong, Shelley Xiuli (International journal of language & communication disorders, 2023)
Background Face‐to‐face class suspensions during the coronavirus disease (COVID‐19) pandemic in 2019 increased telepractice in speech and language therapy. However, little is known about speech and language therapists’ (SLTs) perceived effectiveness of telepractice and its antecedents. Aims To examine the use of telepractice and the factors affecting its perceived effectiveness in Hong Kong mainstream schools during COVID‐19. Methods & Procedures Seventy‐two school‐based Hong Kong SLTs completed a 110‐item online survey with six structural components: (1) concerns, (2) adoption, (3) student selection criteria, (4) perceived effectiveness, (5) continuous professional development and (6) attitudes/beliefs. Outcomes & Results Over 90% of respondents adopted telepractice during the pandemic. Confirmatory factor analysis identified reliable constructs from their component measures. These participants reported great telepractice difficulties (especially in therapy preparation and managing students’ attention and/or communication). Mixed‐response analysis revealed that psychosocial factors (i.e., students’ engagement and SLTs’ attitudes towards telepractice) but not professional practice skill factors (i.e., student client selection criteria and SLTs’ years of experience in school settings) contributed to SLTs’ self‐perceived effectiveness of telepractice. Conclusions & Implications Our findings suggest that psychosocial factors play a more important role than professional practice skill factors in the self‐perceived effectiveness of telepractice. WHAT THIS PAPER ADDS What is already known on the subject Previous surveys reported that although SLTs were interested in using telepractice before the COVID‐19 pandemic, they showed concern about its effectiveness, resulting in a low adoption rate. One critical question naturally arises: What factors may affect the perceived effectiveness of telepractice by SLTs? What this paper adds to existing knowledge This study demonstrates for the first time that despite the high adoption rate of telepractice during the COVID‐19 pandemic, school‐based SLTs exhibited great difficulties, and the SLTs’ self‐perceived effectiveness of telepractice was related to psychosocial factors instead of professional practice skill factors. What are the potential or actual clinical implications of this work Professional support is needed to alter the attitudes of SLTs towards telepractice for enhancing their self‐perceived effectiveness and positive clinical practice experience.